The role of steroidogenic factor-1 (SF-1) in gonadotropin-releasing hormone (GnRH) receptor gene regulation - Pheiffer, Carmen P (Division of Chemical Pathology, 2018)
Gonadotropin releasing hormone (GnRH) is a key reproductive hormone in vertebrates and exerts its effects via the GnRH receptor (GnRHR) to result in the synthesis and release of the gonadotropin hormones in the pituitary gonadotrope cells. GnRHR expression is likely to be regulated in a tissue- and cell- specific manner. A variety of hormones, including GnRH itself, estrogen, progesterone, inhibin, and testosterone have been shown to regulate GnRHR expression. Steroidogenic Factor-1 (SF-1), a member of the orphan nuclear receptor transcription factor family, regulates the expression of both the gonadotropin hormones in the pituitary and the steroidogenic enzymes in the gonads and adrenal gland, and provides a potential molecular mechanism for coordinate control of reproductive function. SF-1 binds to a gonadotrope-specific element (GSE) in the promoters of the gonadotropin hormones. Our studies involved investigating whether SF- I plays a role in tissue-specific regulation of GnRHR gene expression. A genomic clone of the mouse GnRHR gene contains a putative SF- I site at about -15 relative to the translation start site. We demonstrate the presence of a factor with SF-1-like DNA-binding activity in the gonadotrope cell lines, αT3-1 and αT4, by gel retardation assays. DNasel footprinting reveals that the major DNA-binding activity in αT3-1 cells on the GnRHR promoter occurs at the SF-1-like site. The SF-1-like sequence specificity of the interaction is demonstrated by gel redardation and DNasel footprinting assays using specific and mutated oligonucleotides as competitors. Northern blot analysis suggests that GnRHR expression is not solely dependent on the presence of SF-1, as αT4 cells do not express GnRHR but a SF-1 transcript is seen in these cells. Promoter function was analysed by constructing plasmids containing 563 bp of the GnRHR gene 5' to the ATG translation start site linked to a luciferase reporter gene, followed by transfection of these constructs into different cell lines. In addition, a mutant construct containing a mutated SF-1 site was tested. We demonstrate that this 563 bp of the GnRHR gene contains strong promoter activity in both pituitary gonadotrope (αT3-1) and somatotrope (GH₃) cells, but not in non-pituitary (COS-1) cells. Thus promoter activity appears to be tissue specific but not gonadotrope specific. The presence of a mutated SF-1 site in the 563 bp GnRHR gene fragment did not significantly effect the promoter activity, showing that binding of SF-1 protein to this site is not necessary for high levels of GnRHR expression in the pituitary gonadotropes.